2014
DOI: 10.1177/1533317513520213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Person-Centered Care Approaches to Dementia Care on Staff

Abstract: Person-centered care (PCC) has been the subject of several intervention studies reporting positive effects on people with dementia. However, its impact on staff remains unclear. The purpose of this systematic review was to assess the impact of PCC approaches on stress, burnout, and job satisfaction of staff caring for people with dementia in residential aged care facilities. Research articles published up to 2013 were searched on PubMed, Web of Knowledge, Scopus, and EBSCO and reference lists from relevant pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 38 publications
2
89
0
3
Order By: Relevance
“…The literature shows that the person-centered care increases staff's job satisfaction through improved communication between the staff and residents and among the staff [7]. Job satisfaction was used to examine the convergent validity with KPCQ-S. Job satisfaction was measured using the Korean version of COPSOQ II (COPSOQ-K) [24], which was originally developed by the National Institute of Occupational Health in Denmark [23] and modified by June et al, [24].…”
Section: ) Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that the person-centered care increases staff's job satisfaction through improved communication between the staff and residents and among the staff [7]. Job satisfaction was used to examine the convergent validity with KPCQ-S. Job satisfaction was measured using the Korean version of COPSOQ II (COPSOQ-K) [24], which was originally developed by the National Institute of Occupational Health in Denmark [23] and modified by June et al, [24].…”
Section: ) Job Satisfactionmentioning
confidence: 99%
“…The small-scale nursing homes (NHs) have also improved residents' quality of life by allowing residents to have more comfortable and individualized care [6]. Regarding the staff outcomes, the improvement of communication with residents decreased the staff's burnout and emotional exhaustion from work, increased their job satisfaction [7], and enhanced their confidence and ability by providing individualized care to residents based on the philosophical change of person-centeredness [8].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review of person-centered care studies in residential settings identified two randomized controlled trials (RCTs) that demonstrated success in reducing dementia care workers' stress, burnout, and job dissatisfaction (Barbosa et al, 2014). This would suggest that person-centered approaches focusing on the care recipient might also benefit the family, as was demonstrated with Mr. Larsen's family.…”
Section: Effects On Caregiversmentioning
confidence: 91%
“…The greatest threat to personhood may be dementia, where one's sense of self, sometimes challenged by a varying awareness of declining memory and the ability to learn new things as dementia progresses, further "devolves" through negative interactions with others (Barbosa, Sousa, Nolan, & Figueiredo, 2014). Kitwood recognized this challenge and applied the concepts of person-centeredness to dementia care (Kitwood, 1997).…”
mentioning
confidence: 98%
“…Due to the low levels of function that people with dementia have (Fox, Henwood, et al, 2014a;Sterke et al, 2010) physical function should relate to the desires and needs of the individuals, which would connect the reality of people with dementia. This would also align assessment of physical function with consumer directed care model (Barbosa, Sousa, Nolan, & Figueiredo, 2014;Buntin et al, 2006). Furthermore, it has previously been established that while common mortality trajectories exist, where a decline in physical function is one aspect of this (Kelley, Ettner, Morrison, Du, & Sarkisian, 2012) these trajectories are largely individual (Lunney, Lynn, Foley, Lipson, & Guralnik, 2003).…”
Section: Discussionmentioning
confidence: 99%